2019
DOI: 10.31489/2019no1/99-108
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Environment on the Contact Potential Difference of Metal Machine Parts

Abstract: In this paper we consider the influence of environmental parameters on the electrons work function and the contact potential difference of metal parts of machines. Experimental studies have been carried out, including measurements of the contact potential difference on samples from Al, Ti and Ni by the Kelvin-Zisman method at different temperatures, pressures and relative humidity, as well as in non-equilibrium and equilibrium environmental conditions. Measurements of the contact potential difference were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Aircraft structures have requirements as to internal delamination area depending on its detection time through visual or instrumental methods. Each structure may have individual requirements depending on applied testing methods and compulsory inspection periods [8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Aircraft structures have requirements as to internal delamination area depending on its detection time through visual or instrumental methods. Each structure may have individual requirements depending on applied testing methods and compulsory inspection periods [8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…The measurement complex of the contact potential difference developed by the authors of [14] is shown in Fig. 3.…”
Section: Work Function Surface Energy and Properties Of Zrticrnicu Coatingsmentioning
confidence: 99%
“…В координатах μ/μ 0 ~ 1/h экспериментальная кривая спрямляется в соответствии с формулой (1) Здесь T m -температура плавления сплава, σповерхностное натяжение (энергия) покрытий, КРП -контактная разность потенциалов покрытий, φ -работа выхода электронов. Последние две величины определялись нами по прибору, описанного в работе [9].…”
Section: а) б) рисунок 1 -зависимость микротвердости от толщины (а) иunclassified